2021
DOI: 10.1021/acs.jafc.1c00151
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pesticide Uptake Modeling into Potatoes: Considering Tuber Growth Dynamics

Abstract: To explore pesticide uptake from soil into a growing potato, a moving-boundary dynamic model is proposed on the basis of the radical diffusion process of a chemical to a sphere. This model, which considers the logistic growth of the potato tuber, describes two hypothetical processes of chemical diffusion within a growing tuber. The model was tested in an illustrative case study for an application of chlorpyrifos. Results indicate that the distribution of chlorpyrifos concentrations along the potato radius is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…The reason for relatively wide measurement ranges could be due to different compositions (e.g. lipid and water contents) of the periderm for different types of potatoes 38 . As this study aimed to introduce a periderm‐based modeling framework for the plant uptake of pesticides, some input variables such as periderm and medulla compositions were taken from current literature as default values, 42,43 which should be adjusted according to different types or varieties of potatoes when comparing model results to specific potato varieties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for relatively wide measurement ranges could be due to different compositions (e.g. lipid and water contents) of the periderm for different types of potatoes 38 . As this study aimed to introduce a periderm‐based modeling framework for the plant uptake of pesticides, some input variables such as periderm and medulla compositions were taken from current literature as default values, 42,43 which should be adjusted according to different types or varieties of potatoes when comparing model results to specific potato varieties.…”
Section: Resultsmentioning
confidence: 99%
“… (days −1 ) is the growth rate of the potato medulla and (days −1 ) is the degradation rate of the pesticide in the potato medulla, which is approximated using . 38 By replacing by according to Eqn ( 1 ), Eqn ( 2 ) can be solved with the initial condition of 0 as: where is the bioconcentration factor of the pesticide in potato medulla ( ) for the nonperiderm model, which is defined as the ratio of to at a given time step. We note that the term BCF describes the bioaccumulation of pesticide in organisms (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pesticides play important roles in controlling plant diseases, weeds and insects to ensure crop productivity and promote the sustainable development of agriculture [ 1 , 2 , 3 ]. It has been reported that nearly 3.5 million tons of synthetic pesticides are applied every year to control pests worldwide [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%